Calculating pain sensation in neuropathies - A. Soufla; M. Schmelz; R. Rukwied; P. Kokotis (Нервно-мышечные болезни, 2024)
Aim. Evaluating pain sensation after C nociceptor activation with transdermal sinusoidal current wave stimulation protocol and skin biopsy.Materials and methods. Healthy volunteers aged 20–30 years (17 females and 18 males) participated after having given their informed consent. Half‑sine wave pulses of 0.5 sec duration (1 Hz) were generated at intensities of 0.2 to 1 mA by a constant current stimulator. Apart from half‑sine wave stimulation, sine wave pulses of 60 sec duration (4 Hz) were generated at intensity of 0.2 mA also by the constant current stimulator (Digitimer Ltd, Welwyn Garden City, UK) controlled by DAPSYS 8 (www.dapsys.net). Moreover, we performed 3‑mm skin punch biopsies 10 cm above the lateral malleolus of the leg and in the middle of the volar side of the forearm to the volunteer’s group.Results. Delivering transdermal sinusoidal half‑sine wave when trying to stimulate mechano‑sensitive C fibers, when the amplitude of the delivered wave is increased from 0.2 to 1 mA according to our protocol, pain sensation is also increased following the same scheme. If we observe a different scheme of activation in C fibers, this could be a sign of neuropathic pain. Considering the mechano‑insensitive C fibers of pain, when trying to stimulate them we expect increasing pain sensation and then familiarization, desensitization and reduction of pain sensation. As a result, if this scheme isn’t observed when sine wave is delivered transdermal with 1 min of duration, and we observe a different scheme, a C fiber neuropathy and neuropathic pain could be involved. Regarding the skin biopsies, a correlation between pain sensation of sine wave (delivered transdermal to stimulate mechano‑insensitive C fibers of pain on the forearm), and the nerve fiber density was observed. A correlation between the bifurcated fibers of the biopsy site and the pain sensation was observed when mechanosensitive and mechano‑insensitive fibers are stimulated, which needs further investigation. Also, a correlation between the remnant nerve fibers of subepidermal nerve plexus and mechano‑insensitive nerve fibers of pain is observed that also needs further investigation.Conclusion. Skin biopsy and transdermal electrical stimulation are very promising available tools of diagnosing C fiber neuropathies and assessing neuropathic pain.